2018
DOI: 10.1111/jvim.15291
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the mucosal microbiota to gastrointestinal inflammation and small cell intestinal lymphoma in cats

Abstract: BackgroundThe gastrointestinal (GI) microbiota in healthy cats is altered in IBD. Little research has been performed to identify whether specific bacterial groups are associated with small cell GI lymphoma (LSA).HypothesisMucosal bacteria, including Enterobacteriaceae and Fusobacterium spp., are abundant in intestinal biopsies of cats with small cell GI LSA compared to cats with IBD.AnimalsFourteen cats with IBD and 14 cats with small cell GI LSA.MethodsRetrospective case control study. A search of the medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 77 publications
0
41
1
Order By: Relevance
“…Dogs with chronic enteropathy (CE) have been shown to have lower concentrations and altered patterns of SCFAs, as well as changes in the fecal microbiota compared to healthy dogs (Minamoto et al, 2019). With respect to cats, it has been shown that the GI microbiota in those with IBD is altered compared to healthy cats (Garraway et al, 2018). One study also found that Fusobacterium spp.…”
Section: Inflammatory Enteropathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Dogs with chronic enteropathy (CE) have been shown to have lower concentrations and altered patterns of SCFAs, as well as changes in the fecal microbiota compared to healthy dogs (Minamoto et al, 2019). With respect to cats, it has been shown that the GI microbiota in those with IBD is altered compared to healthy cats (Garraway et al, 2018). One study also found that Fusobacterium spp.…”
Section: Inflammatory Enteropathiesmentioning
confidence: 99%
“…One study also found that Fusobacterium spp. are elevated in the ileum and colon of biopsies from cats with small cell GI lymphoma compared to those with IBD; however, it’s not yet clear whether this change plays any role in the development of GI lymphoma ( Garraway et al, 2018 ). While a number of previous reviews have discussed this topic at length ( Heilmann and Allenspach, 2017 ; Redfern et al, 2017 ; Roth-Walter et al, 2017 ; Yogeshpriya et al, 2017 ; Barko et al, 2018 ), few authors have explicitly evaluated the impact of macronutrient nutrition (nutrition supplied by carbohydrates, protein, and fat), digestion, and food processing on the pet microbiome and its subsequent effect on health outcomes in IBD.…”
Section: Current Evidence: the Role Of Nutrition In Influencing Cat Amentioning
confidence: 99%
“…Although the relationship between intestinal dysbiosis and colorectal cancer has been widely debated in humans, only a small number of studies have been focused on the correlation between bowel cancer and gut microbiota in dogs and cats and, what is more, with discordant results (Omori et al ., 2017; Garraway et al ., 2018; Gavazza et al ., 2018; Herstad et al ., 2018). However, while the relative abundance of the Fusobacterium genus and the Enterobacteriaceae family increased in ileum and colon biopsies from cats with small cell GI lymphoma (Garraway et al ., 2018), no differences of the abundance of these two bacterial taxa were observed in dogs affected by intestinal lymphoma when compared to the control (Omori et al ., 2017; Gavazza et al ., 2018; Herstad et al ., 2018) and even one study reported a decreased abundance of Fusobacterium spp. in canine lymphoma biopsies (Gavazza et al ., 2018).…”
Section: The Canine and Feline Gut Microbiota And Gi Diseasesmentioning
confidence: 99%
“…There is a dynamic relationship between the immune system and microbiota. Intestinal mucosa, with Tolllike receptors, induces fall signal and provokes the production and the release of inflammatory mediators (cytokines, phagocytes) (Schmitz and Suchodolski, 2016;Garraway et al, 2018).…”
Section: Role Of the Physiological Gut Microbiotamentioning
confidence: 99%